THE LEVEL OF MATERNAL KNOWLEDGE ABOUT GIVING VITAMIN A TO TODDLERS AT NOVI LINTAS TIMUR'S MIDWIFE CLINIC PANYABUNGAN DISTRICT, KOTA REGENCY CHRISTMAS MANDAILING YEAR 2022 - HELMI WARDAH NASUTION; FERIKA DESI (JURNAL ILMIAH SIMANTEK, 2023)
According to the WHO (World Health Organization) among pre-school children, it is estimated that there are as many as 6-7 million new cases of xeropthalmia every year, approximately 10% of whom suffer corneal damage. Health problems in Indonesia risk Vitamin A deficiency (KVA) from the target number of 20 million toddlers. Prevalences of KVA based on a 1992 vitamin A survey showed xerapthalmia of 0.33%, but sublinically the prevalence of KVA ( serum retinol levels in the blood) in toddlers was 50%. The purpose of this study was to determine the level of maternal knowledge about giving vitamin A to toddlers. The research starts from January 2022 , What is descriptive by using primary data collected through questionnaires and this study is by random sampling with a population of 139 mothers and a sample of 58 people. This research was carried out at the Novi Lintas Timur midwife clinic, Panyabungan District, Mandailing Natal Regency in 2022. From the results of this study, it was shown that the majority of mothers of toddlers who had a lack of knowledge level were 43 people (74%), the minority who were knowledgeable enough as many as 5 people (8%). It is hoped that mothers who have toddlers should pay more attention to giving vitamin A to their children because at this time there are still many mothers who do not understand the importance of vitamin A in toddlers.